Use of psychoeducation in the treatment of bipolar disorder. (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
Bipolar disorder shows significant chronicity and severity of symptoms usually causing psychosocial damage. Pharmacological treatment is considered essential for bipolar patients. However, in the psychosocial field, an association between stressors and precipitation of bipolar episodes has been clearly documented, highlighting the need for intervention in this field. As for psychoeducation, this consists of a psychosocial intervention model. The present study aimed to investigate scientific literature in respect of the outcomes of psychoeducation as a part of the treatment for bipolar disorder. Psychoeducation is seen to be a successful model in the adherence to psychopharmacological treatment, in the greater awareness and understanding of this disorder, by decreasing the number of maniac episodes as well the number of relapses and hospitalizations, improving coping and social skills. In the same way, psychoeducation offers an important alternative for the relatives of bipolar patients. It may be concluded that psychoeducation is not a substitute for pharmacological treatment, but, it has been effective in a significant optimization of the effects of pharmacological treatment.
Keywords: Psychoeducation; Clinical intervention; Bipolar Disorder; Review